Argument Clauses in Sahidic Coptic - Grossmann, Eitan (Zeitschrift für ägyptische Sprache und Altertumskunde, 2009)
In response to recent claims regarding the syntactic influence of Greek on Coptic, the present article argues that the empirical basis for such claims is founded on a misconception of Coptic syntactic structure. Specifically, the assumed complementary distribution between e -+infinitive and e -+causative infinitive is shown to be fallacious, and it is demonstrated that these two are found in mutually opposed constructions. In this context, it is argued that the causative infinitive, contrary to the claims found in grammatical literature, does mark causativity when opposed to other constructions. Additional argument clause types, which are generally neglected in grammars, are briefly surveyed.